StevaPro Professional Sports Video Analysis Tool (2012)
The combined technology teams have been working together to create new and enhanced service platforms including the automation of video indexing through each company's existing software platforms. As we work towards merging the technologies of STEVA Sports Software and Pointstreak, the combined result will ultimately create the capability of automating the indexing of video based on scored game events. The STEVA Video Network or "SVN" is an additional service that is available to teams and leagues who want to publish video directly to our network for distribution to virtually anyone connected to the web. Inside STEVA's line of software products you can send video to the web at the push of a button. Hockey, Soccer, Basketball, Lacrosse, Volleyball